FINANCIAL PERFORMANCE, ENVIRONMENTAL DISCLOSURE, AND FIRM VALUE: THE MODERATING ROLE OF ECONOMIC GROWTH IN ENERGY SECTOR COMPANIES IN INDONESIA - Kusmayadi, Dedi; Firmansyah, Irman; Dermawan, Wildan Dwi (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2025)
This research aims to explore the financial performance of energy companies and environmental disclosure practices in increasing company value. In addition, to date, there has been no research that investigates the role of economic growth in the relationship between environmental disclosure and corporate performance on corporate value in energy companies, even though economic growth greatly influences business conditions. This is the urgency of this research. Therefore, this research fills the gap by including gross domestic product as an indicator of economic growth as a moderating variable. The method used is moderated regression analysis with the research sample, namely energy companies in Indonesia that made environmental disclosures from 2017 to 2022. The results found that financial performance (profitability, liquidity, activity and solvability) significantly influenced company value, but environmental disclosure was not successful. shows influence. In addition, the moderation analysis test found that GDP moderated the relationship between environmental disclosure and company value, but did not moderate the relationship between financial performance and company value. This model implies that there is a role for the macroeconomic situation that triggers management to disclose its environmental activities in supporting increasing company value in the energy sector.